2017
DOI: 10.1002/hep.29051
|View full text |Cite
|
Sign up to set email alerts
|

An endoplasmic reticulum protein, Nogo‐B, facilitates alcoholic liver disease through regulation of kupffer cell polarization

Abstract: Background Nogo-B (Reticulon 4B) is an endoplasmic reticulum (ER) resident protein that regulates ER structure and function. Since ER stress is known to induce M2 macrophage polarization, we examined whether Nogo-B regulates M1/M2 polarization of Kupffer cells and alters the pathogenesis of alcoholic liver disease (ALD). Methods M1 and M2 phenotypes were assessed in relation to Nogo-B expression and disease severity in liver specimens from ALD patients (NCT01875211). Liver specimens from wild-type (WT) and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…As O-GlcNAcylation is a highly dynamic PTM, acute or chronic changes in O-GlcNAc signaling may lead to different outcomes by modulating different substrates (22). It is also noteworthy that, in our mouse model of ethanol diet-induced liver injury, hepatocyte injury and inflammation were evident, while no obvious fibrosis was developed before the mice were sacrificed (34). The levels of liver O-GlcNAcylation were already decreased significantly in these mice.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As O-GlcNAcylation is a highly dynamic PTM, acute or chronic changes in O-GlcNAc signaling may lead to different outcomes by modulating different substrates (22). It is also noteworthy that, in our mouse model of ethanol diet-induced liver injury, hepatocyte injury and inflammation were evident, while no obvious fibrosis was developed before the mice were sacrificed (34). The levels of liver O-GlcNAcylation were already decreased significantly in these mice.…”
Section: Discussionmentioning
confidence: 65%
“…We also examined the changes in O-GlcNAc levels in a mouse model of ethanol-induced liver injury. Mice were fed with a Lieber-DeCarli liquid diet to induce alcoholic steatosis and liver inflammation (34). Decreased liver O-GlcNAc levels were seen in mice fed with the ethanol diet as compared with the control group, which could be explained by the reduced expression of OGT in ethanol-fed mice ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Increased circulating Nogo‐B has been reported in several different disease states (Gao et al, ; Men et al, ; Sutendra et al, ), whereas Nogo‐B deficiency is known to ameliorate liver fibrosis and portal hypertension by inactivating the TGFβ signalling pathway (Tashiro, Satoh, Utsumi, Chung, & Iwakiri, ; Zhang et al, ) and to reduce alcoholic liver disease by regulating Kupffer cell polarization (Park et al, ). In this study, we found that Nogo‐B might facilitate intrahepatic cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were fasted for 6 hr before sacrifice and tissues were collected for protein and RNA extraction and histology analysis. Ethanol-induced liver injury was induced as described before (35). Briefly, mice were fed with a Lieber-DeCarli liquid diet (F1258SP, BioServ, Flemington, NJ) or a control diet (F1259SP, BioServ) that has a matched calorie with ethanol diet for 6 weeks.…”
Section: Mice and Human Liver Samplesmentioning
confidence: 99%